Beneficial cumulative effects of old parental age on offspring fitness. Issue 1960 (13th October 2021) - Travers, Laura M.; Carlsson, Hanne; Lind, Martin I.; Maklakov, Alexei A.
Abstract : Old parental age is commonly associated with negative effects on offspring life-history traits. Such parental senescence effects are predicted to have a cumulative detrimental effect over successive generations. However, old parents may benefit from producing higher quality offspring when these compete for seasonal resources. Thus, old parents may choose to increase investment in their offspring, thereby producing fewer but larger and more competitive progeny. We show that Caenorhabditis elegans hermaphrodites increase parental investment with advancing age, resulting in fitter offspring who reach their reproductive peak earlier. Remarkably, these effects increased over six successive generations of breeding from old parents and were subsequently reversed following a single generation of breeding from a young parent. Our findings support the hypothesis that offspring of old parents receive more resources and convert them into increasingly faster life histories. These results contradict the theory that old parents transfer a cumulative detrimental 'ageing factor' to their offspring.